Blockchain technology, leadership competencies, and organizational change : A conceptual exploration and future research agenda - Kusi, Samuel Yaw; Shahzad, Khuram; Dan, Sorin (Routledge, 2024)
Building on socio-technical systems (STS) theory, this chapter explores the change processes that organizations go through as they implement blockchain in their operations. The chapter explores the interplay between the adoption of blockchain as a new disruptive technology and organizational change as a process and argues that a new kind of leadership and competencies are required as organizations engage in and carry out organizational change. Yet, the chapter finds that the current theoretical and empirical development of leadership in the context of blockchain adoption remains insufficient. To address this gap, this study proposes a conceptual framework that builds on STS theory and existing literature on organizational change and leadership. It aims to contribute to the existing literature in two main ways. First, it develops a conceptual framework connecting organizational change and leadership competencies, on the one hand, with the specific features of blockchain technology, on the other hand. Second, it derives several propositions and proposes a research agenda for future research on the linkages between organizational change, leadership, and the adoption of an insufficiently understood technology. In so doing, this chapter focuses mainly on what Rost calls the peripheral elements of leadership theory.
Keywords: Blockchain technology; leadership competencies; organizational change; fi=Julkisjohtaminen|en=Public Management|; fi=Tuotantotalous|en=Industrial Management|